(untitled) (Ustozlar uchun, 2026)
This study examines the role of English in modern education and professional development. It analyzes how proficiency in English influences academic performance, career opportunities, international collaboration, and competitiveness in the labor market. The research utilized surveys, observations, and statistical analyses to assess the impact of English language skills on students and professionals. Findings indicate that individuals with strong English skills have better academic outcomes, greater access to professional opportunities, and improved participation in global networks. The study highlights the importance of integrating English language instruction into curricula to enhance educational quality and professional mobility.